221k views
2 votes
Fill in the blanks to make the equation true. (x−9)(x+2)=x^2________ −18

2 Answers

3 votes

Answer:


\large\boxed{-7x}

Explanation:

Use FOIL:

(a + b)(c + d) = ac + ad + bc + bd


(x-9)(x+2)=(x)(x)+(x)(2)+(-9)(x)+(-9)(2)=x^2+2x-9x-18

combine like terms


=x^2+(2x-9x)-18=x^2-7x-18

User Verjas
by
6.6k points
6 votes

Answer:

x² - 7x - 18

Explanation:

Remember to follow FOIL.

First, multiply the first. (x)(x) = x²

Next, multiply the second. (x)(2) = 2x

Then, multiply the third. (-9)(x) = -9x

Finally, multiply the last. (-9)(2) = -18

Combine like terms: x² + 2x - 9x - 18

x² - 7x - 18

x² - 7x - 18 is your answer.

~

User Liloka
by
6.6k points